HLA-DRB1 polymorphisms and alopecia areata disease risk: A systematic review and meta-analysis. Issue 32 (August 2018) - Ji, Conghua; Liu, Shan; Zhu, Kan; Luo, Hongbin; Li, Qiushuang; Zhang, Ying; Huang, Sijia; Chen, Qing; Cao, Yi
Abstract: Background: Published studies have reported conflicting and heterogeneous results regarding the association between human leukocyte antigen ( HLA )- DRB1 polymorphisms and alopecia areata (AA). This study aimed to review and quantitatively analyze the association between HLA - DRB1 polymorphisms and AA. Methods: In this study, all relevant publications were searched through December 2016. Odds ratios (ORs) and confidence intervals (CIs) for comparisons between case and control groups were calculated. Stata 14.0 software was used to perform statistical analysis. This research does not require formal ethical approval because the data used in this analysis do not involve personal information and thus do not affect privacy. Results: Twelve articles were identified. For HLA-DRB1*04 and HLA-DRB1*16 polymorphisms, the OR (95% CIs) was 1.49 (1.24–1.78) and 1.61 (1.08–2.41), and P was <.01 and <.01, respectively. For HLA-DRB1*0301, HLA-DRB1*09, and HLA-DRB1*13 polymorphisms, the OR (95% CIs) was 0.42 (0.28–0.63), 0.74 (0.55–0.99), and 0.62 (0.40–0.98), and P was <.01, <.01, and <.01, respectively. Statistical evidence revealed no publication bias ( P > .05). Conclusion: The present meta-analysis suggested that HLA-DRB1*04 and HLA-DRB1*16 polymorphisms might be associated with increased AA risk, while HLA-DRB1*0301, HLA-DRB1*09, and HLA-DRB1*13 polymorphisms might decrease the AA risk. Studies with adequate methodological quality on gene–gene and gene–environment interactions are needed to validate the results in the future. Abstract : Supplemental Digital Content is available in the text